Motivasi Siswa dalam Pembelajaran Seni Budaya (Musik) Kelas VIII di SMP Negeri 15 Padang - Tri Puti Anggini Rahmania; Robby Ferdian (Misterius : Publikasi Ilmu Seni dan Desain Komunikasi Visual., 2024)
The purpose of this study was to identify and explain what encourages students to study Cultural Arts (Music) in class VIII of SMP Negeri 15 Padang. This research used a qualitative method with a descriptive approach. The researcher became the main instrument in data collection, with the help of stationery and camera. Data were collected through observation, direct interaction, and documentation. Data analysis was carried out by reducing information, presenting findings, and concluding research results. The findings show the low motivation of students in learning Cultural Arts (music) at the grade VIII level, which is caused by the ineffectiveness of the expository teaching method used by the teacher. This is reinforced by findings from interviews which show that students are more inclined towards extrinsic motivation compared to intrinsic motivation. The lack of access to learning media devices such as projectors, laptops and speakers in the school environment is also one of the factors contributing to students' lack of interest in learning Cultural Arts (music) at SMP Negeri 15 Padang.